2009
DOI: 10.1038/ajg.2009.269
|View full text |Cite
|
Sign up to set email alerts
|

Can a Wire-Guided Cannulation Technique Increase Bile Duct Cannulation Rate and Prevent Post-ERCP Pancreatitis?: A Meta-Analysis of Randomized Controlled Trials

Abstract: This meta-analysis shows that the wire-guided technique increases the primary cannulation rate and reduces the risk of post-ERCP pancreatitis compared with the standard contrast-injection method. Further large, well-performed, randomized controlled studies are needed to confirm these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
106
1
6

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(115 citation statements)
references
References 32 publications
2
106
1
6
Order By: Relevance
“…In a meta-analysis of five randomised controlled trials (RCTs), guidewire cannulation was shown to lower post-ERCP pancreatitis (rates 0%-3%) compared to standard contrast-injection method (rates 4%-12%) and increase primary cannulation rates compared to the standard method (OR = 2.05) [19] . A Cochrane meta-analysis of 12 RCTs (3450 patients) similarly found that post-ERCP pancreatitis incidence was lower in the wire-guided cannulation (WGC) group (3.5%) compared to contrast-assisted cannulation technique (6.7%) and primary cannulation rates were higher in the WCG group (84% vs 77%, RR = 1.07).…”
Section: Ercp Techniquementioning
confidence: 99%
“…In a meta-analysis of five randomised controlled trials (RCTs), guidewire cannulation was shown to lower post-ERCP pancreatitis (rates 0%-3%) compared to standard contrast-injection method (rates 4%-12%) and increase primary cannulation rates compared to the standard method (OR = 2.05) [19] . A Cochrane meta-analysis of 12 RCTs (3450 patients) similarly found that post-ERCP pancreatitis incidence was lower in the wire-guided cannulation (WGC) group (3.5%) compared to contrast-assisted cannulation technique (6.7%) and primary cannulation rates were higher in the WCG group (84% vs 77%, RR = 1.07).…”
Section: Ercp Techniquementioning
confidence: 99%
“…29 Systemic analyses suggest that WGC is more successful and associated with less PEP when compared to catheter and contrast injection. [68][69][70][71] The risk of PEP is similar for both cannulation techniques when pancreatic stenting is allowed, however the protective effect of WGC is negated when trainees are involved. 70 There are two methods of WGC.…”
Section: Procedures Techniquesmentioning
confidence: 97%
“…Most trials and meta-analyses suggest that WGC lowers rates of post-ERCP pancreatitis compared with the classic cannulate and inject method, which is largely historical ( 11 ). However, during GWC intended for the bile duct, inadvertent passage of a wire in the PD is relatively common, though oft en dismissed as inconsequential.…”
Section: Editorialmentioning
confidence: 99%